Desenvolvimento vegetativo de porta-enxertos de videira em condições subtropicais - Silva, Tania Pires da (2008)
The aim of the work was to evaluate the phytotechnical performance of different rootstocks in the formation level on field conditions and the initial development of the graft, as well as the application of auxiliaries technicians to the root potential increment of the rootstocks cuttings of VR 043-43 in nursery conditions. Ligneous cuttings from grapevine VR 043-43 , measuring 20 cm, were stratified for 48h (under the temperature of 4 oC), part of the cuttings were kept under environment temperature (25 } 5 oC). All the cuttings were treated with indolbutyric acid (IBA) in different concentrations of 0, 1.000, 2.000 and 3.000 mgL-1, associated and not associated to boric acid at concentration of 150 μg L-1 for 10sec. The cuttings were planted into polyethylene plastic bags (capacity of 2,5L), filled with clay soil. They were kept in nursery made of shading screen providing 50% of luminosity. The evaluations occurred 120 days after the experiment deployment. In November, the seedlings originated from the rooted cuttings of 17 grapevine rootstocks ( SO4 , Teleki 8B , Harmony , Golia , Riparia de Traviu , Paulsen , 420 A , 99R , 5C , RR101-14 , Kober 5BB , Rupestris Du Lot , IAC 313 Tropical , IAC 766 Campinas , IAC 572 Jales , VR 043-43 and IAC 571-6 Jundiai ) were taken to the field under subtropical conditions (24o33 40 S and 54o04 12 W, 420 m height and Cfa Koppen climate, with annual maximum average temperature of 28,5 oC and minimum of 17,5 oC). After four months, it was evaluated the anthracnose and rust severity on the grapevine leaf sprouting from the rootstocks and more five months of vigor (total branch number, average diameter, biggest branch length and total leaf area fresh mass). In the sequence, it was performed winter graft using BRS Violeta . The evaluated characteristics for this part of the experiment were percentage of tissue union, diameter and graft average length, which happened after 60 days of grafting. It was concluded that the stratification of the cutting is not fundamental to increase the efficiency of the rooting process of the rootstock VR 043-43 . The cuttings should only be treated with IBA at 3.000 mg L-1 in association to boric acid. The rootstocks IAC 572 Jales and IAC 313 Tropical were resistant to the anthracnose and rust. The rootstock IAC 572 Jales was the one that showed greater performance on field, before grafting. The rootstocks SO4 , Harmony , Paulsen and IAC 766 Campinas showed greater vigor to the development of the graft BRS Violeta